Motivational interviewing to improve adherence behaviours for the prevention of diabetic foot ulceration. Issue 2 (19th December 2018) - Binning, Jodi; Woodburn, Jim; Bus, Sicco A.; Barn, Ruth
Summary: Diabetic foot ulceration is a major complication associated with high morbidity. Little evidence exists on which interventions are effective at preventing ulceration. Participants who are adherent to self‐care behaviours have significantly better outcomes. Motivational interviewing is an intervention that has been used successfully for conditions where adherence is important, such as reduction of obesity and HbA1c levels. A systematic review was conducted to determine whether motivational interviewing is effective at improving adherence for the prevention of Diabetic Foot Ulceration. Electronic searches were run without date or language restrictions in MEDLINE (viaEBSCOhost), CINAHL (viaEBSCOhost), ProQuest (Health and Medical Collection, Nursing and Allied Health Database, PsycINFO, Psychology, PsychArticles), AMED, EMBASE, Cochrane Central Register of Controlled Trials, ScienceDirect, and Web of Science Core Collections. Papers were included if participants had or were at risk of diabetic foot ulceration. Studies required motivational interviewing or a motivational approach as the sole intervention or as a component. Randomised controlled trials and quasi‐experimental studies were included if ulceration and/or at least one behavioural outcome was measured before and after the intervention. Five studies met the inclusion criteria. Heterogeneity prevented the pooling of data. One study used motivational interviewing as the sole intervention. This study found a short‐term positive effect on footwear adherence. The remaining four studies had a motivational component within their interventions. Two of these studies showed the intervention to be effective but both were at a high risk of bias. This review demonstrates an evidence gap. More research is needed.